Murine transgenic embryonic stem cell lines for the investigation of sinoatrial node-related molecular pathways - Mellein, Stefanie; Sumer, Simon; Jauch, Anna; Rolletschek, Alexandra; Niesler, Beate; Rappold, Gudrun; Hoffmann, Sandra (Stem cell research, 2017)
The elucidation of molecular mechanisms that restrict the potential of pluripotent stem cells and promote cardiac lineage differentiation is of crucial relevance, since embryonic stem cells (ESCs) hold great potential for cell based heart therapies. The homeodomain transcription factor Shox2 is essential for the development and proper function of the native cardiac pacemaker, the sinoatrial node. This prompted us to develop a cardiac differentiation model using ESC lines isolated from blastocysts of Shox2-deficient mice. The established cell model provides a fundamental basis for the investigation of molecular pathways under physiological and pathophysiological conditions for evaluating novel therapeutic approaches.